2009
DOI: 10.1109/tsp.2009.2025797
|View full text |Cite
|
Sign up to set email alerts
|

Joint Bayesian Endmember Extraction and Linear Unmixing for Hyperspectral Imagery

Abstract: Abstract-This paper studies a fully Bayesian algorithm for endmember extraction and abundance estimation for hyperspectral imagery. Each pixel of the hyperspectral image is decomposed as a linear combination of pure endmember spectra following the linear mixing model. The estimation of the unknown endmember spectra is conducted in a unified manner by generating the posterior distribution of abundances and endmember parameters under a hierarchical Bayesian model. This model assumes conjugate prior distributions… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
293
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 333 publications
(296 citation statements)
references
References 54 publications
(150 reference statements)
2
293
0
1
Order By: Relevance
“…Statistical methods: In the statistical framework, spectral unmixing is formulated as a statistical inference problem by adopting a Bayesian methodology where the inference engine is the posterior density of the random objects to be estimated as described for example in [20,21,22].…”
Section: Related Workmentioning
confidence: 99%
“…Statistical methods: In the statistical framework, spectral unmixing is formulated as a statistical inference problem by adopting a Bayesian methodology where the inference engine is the posterior density of the random objects to be estimated as described for example in [20,21,22].…”
Section: Related Workmentioning
confidence: 99%
“…Recently, this assumption has been relaxed by applying a single step hierarchical Bayesian approach, called Bayesian linear unmixing (BLU). The resulting algorithm required the number R of factors to be specified (see [10] for details). Here we extend BLU to a fully unsupervised algorithm that generates samples distributed according to the joint posterior distribution of R and the other model parameters, from which a Bayesian estimator of R can be derived.…”
Section: Mathematical Modelmentioning
confidence: 99%
“…The BLU algorithm studied in [10] generates an estimate of the posterior distribution of M and A given the number R of factors for appropriate prior distributions assigned to the mixing parameters in (1). Moreover, the residual errors in (1) are assumed to be independent identically distributed (i.i.d.)…”
Section: Unsupervised Bayesian Linear Unmixingmentioning
confidence: 99%
See 1 more Smart Citation
“…Dobigeon and Brun [7] compared the results obtained by applying PCA, independent component analysis (ICA) [8], vertex component analysis (VCA) [9], and Bayesian linear unmixing (BLU) [10] to experimental EELS-HSI data. They eventually found that BLU provided the most plausible spatial distributions for the constituent spectral components, presumably because of its more realistic modeling of the EELS-HSI data.…”
Section: Introductionmentioning
confidence: 99%